Advertisement and aggressive calls of Ischnocnema oea (Heyer, 1984) (Anura, Brachycephalidae) - Hepp, Fabio; Canedo, Clarissa (Zootaxa, 2013)
Ischnocnema oea (Heyer, 1984) is one of the 10 species recognized within the I. guentheri series (Canedo & Haddad 2012). Within this series, the advertisement call is known for: I. gualtheri (Heyer 1984); I. guentheri (Heyer 1984, Heyer 1990, Kwet & Solé 2005, and Gehara et al. 2013); I. henselii (Kwet & Solé 2005, and Gehara et al. 2013); I. izecksohni (Taucce et al. 2012); and I. nasuta (Heyer 1984). The aggressive call is known for I. guentheri and I. henselii (Kwet & Solé 2005). Here, we provide the first description of the advertisement and aggressive calls of I. oea.